Assessing the mediating role of student engagement on the relationship between student interactions and student performance in entrepreneurship education (Global Business Management Review (GBMR), 2024)
Previous literature suggested that more studies are needed in the context of technology mediated learning in entrepreneurship education. Hence, this study aims is to gauge the understanding of the factors influencing student performance for the Fundamentals of Entrepreneurship (ENT300) subject. This study is underpinned by the Social Learning Theory: Groups, Nets, and Sets. This study was conducted in the Universiti Teknologi MARA Perlis Branch (UiTM Perlis) using survey. 281 students had participated in this study. Data were analyzed using SmartPLS. Since the research model for the study was reflective-formative, the second order approach was used to assess the structural model.  The results of this study reveal positive influence between Student Interactions and Student Engagement, as well as between Student Engagement and student performance variables (Satisfaction, Efficiency, and Effectiveness). Also, Student Engagement plays a significant role as a mediator between Student Interactions and student performance variables. This study contributes to the literature of the development of Social Learning Theory: Groups, Nets, and Sets. Finally, this study makes practical contributions to the higher learning institution that plans to use a technology mediated learning approach for large enrolment subject.